AN ANALYSIS OF INDONESIAN-ENGLISH CODE-MIXING FOUND IN BANTEN - Irma Eka Pratiwi; Eulis Rahmawati; Siti Sa’diah (Journal of English Language Teaching and Literature (JELTL), 2023)
This research intends to analysis the types of code-mixing in Banten employed by 2nd grade students of SMAN 2 Kota Serang, to know the factors of students used code-mixing, to know the reasons of students used code-mixing. The mixed method was used. To obtain the data observation, questionnaire, and interview were employed. The result showed all 2nd grade students of XI MIPA 4 used code mixing. The types of code mixing used by students were morphemes, word, modifiers, phrase, clause, sentences. The factors of students doing code mixing were participation roles and relationship, situational factor, message intrinsic factor, and language attitude, dominance attitude, and security attitude factors. While the reasons that cause the students used code mixing were talking about certain topics, quoting others, be firm about something (express solidarity), interjection (inserting sentence filler or sentence conjunction), repetition is used for communication, intention to clarify speech content or speech, expressing group identity. Therefore, It is visible the students used code mixing in their activities.